Dermaseptin-PH: A Novel Peptide with Antimicrobial and Anticancer Activities from the Skin Secretion of the South American Orange-Legged Leaf Frog, Pithecopus (Phyllomedusa) hypochondrialis - Huang, Linyuan (Molecules, 2017)
The dermaseptin peptides, mainly derived from the skin secretions of Hylidae frogs, belong to a superfamily of antimicrobial peptides and exhibit diverse antimicrobial and anticancer activities with low cytotoxicity. Here, we reported a novel dermaseptin peptide, from the South American orange-legged leaf frogs, Pithecopus (Phyllomedusa) hypochondrialis, processing the shortest peptide length, namely Dermaseptin-PH. The complementary DNA (cDNA) encoding biosynthetic precursor of Dermaseptin-PH was initially identified by the rapid amplification of cDNA ends PCR (RACE-PCR) technique from the skin secretion. The predicted primary structure was confirmed by a combination of reverse-phase high performance liquid chromatography (RP-HPLC) and MS/MS fragmentation from the skin secretion. Chemically-synthetic Dermaseptin-PH was investigated using a range of bioactivity assessment assays to evaluate the biological activities and cytotoxicity of Dermaseptin-PH. Dermaseptin-PH inhibited the growth of Gram-negative bacteria, Gram-positive bacteria, and pathogenic yeast Candida albicans. In addition, Dermaseptin-PH showed a broad-spectrum of anticancer activities against several cancer cell lines including MCF-7, H157, U251MG, MDA-MB-435S, and PC-3. The potent antimicrobial and anticancer activities of Dermaseptin-PH make it a promising candidate in the discovery of new drugs for clinical applications, and the relatively short sequence of Dermaseptin-PH can provide new insight for the research and structural modification of new peptide drugs.